Late Weichselian to early Holocene vegetation and bird activity on Andøya, Nordland County : as evidenced primarily by macrofossils - Elverland, Ellen (University of Tromsø, 2012)
The papers of this thesis are not available in Munin: 1. Elverland, E. & Alm, T.: 'High resolution macrofossil analysis of Late Weichselian Arctic lacustrine sediments on Andøya, northern Norway' (manuscript) 2. Elverland, E., Bjerke, J.W. & Alm, T.: 'Is one core enough? A study of the intrasite macrofossil variability of a Late Weichselian lacustrine record on Andøya, North Norway' (manuscript) 3. Alm, T. & Elverland, E.: 'A Late Weichselian Alle alle colony on Andøya, northern Norway : a contribution to the history of an important Arctic environment' (manuscript) 4. Parducci, L., Jørgensen, T., Tollefsrud. M.M., Elverland, E., Alm, T., Fontana, S.L., Bennett, K.D., Haile, J., Matetovici, I., Suyama, Y., Edwards, M.E., Andersen, K., Rasmussen, M., Boessenkool, S., Coissac, E., Brochmann, C., Taberlet, T., Houmark-Nielsen, M., Krog-Larsen, N.,Orlando, L., Gilbert, M.T.P., Kjær, K.H., Alsos, I.G. & Willerslev: 'Glacial Survival of Boreal trees in Northern Scandinavia', Science (2012) vol.335 no.6072:1083-1086. Available at http://dx.doi.org/10.1126/science.1216043 This thesis shows that Late Weichselian vegetation on Andøya may have been more diverse than previous studies have revealed. The thorough investigation of macrofossils in four parallel cores provides more reliable evidence for interpreting changes in vegetation cover than reconstructions based on a single core. The botanical macrofossils retrieved in this study largely support previous studies at the northern tip of Andøya. Arctic plant communities, probably dominated by Papaver and several species of Poaceae and Brassicaceae characterized the area. Climatic ameliorations occurred at c. 22 000 – 20 100, 20 100 – 19 500, 19 500 – 19 200, 18 800 – 18 100, 17 500 – 16 800 and 15 100 – 14 500 cal. yr BP, and during these ameliorations, the vegetation may have been more diverse than recorded both in the pollen- and macrofossil material. Macrofossils (bones) of little auk (Alle alle), coupled with other evidence, suggest a longlasting ...